The development of inquiry-based learning unit on exoplanet detection for high school & undergraduate - Wachiraporn Choopan (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
This research aimed to develop inquiry-based learning units and models for detecting exoplanets in order to promote student understanding by focusing on transit and radial velocity methods. The models represent the methods for detecting exoplanets in two main ways consistent with the fact revealed by astronomical measurements. With respect to teaching students, the developed learning units and models for detecting exoplanets were developed to teach 30 grade 11 students in science and six first-year undergraduate students from biomedical engineering class. The data collection tools included both quantitative and qualitative tests, questionnaires, and open-ended questions to assess the knowledge and attitudes of students. Results from the analysis showed that the developed units incorporated with models can be used to enhance student's understanding on exoplanet detection. It was evident when the students were able to gain self-knowledge by designing their own experiments by modifying variables such as the distance between the planets and their stars in order to compare the results. Moreover, the evaluation found that students had a positive attitude the towards learning units because the students had freedom to study by themselves.